A review of static and dynamic heliostat wind loads. (1st September 2021) - Emes, Matthew; Jafari, Azadeh; Pfahl, Andreas; Coventry, Joe; Arjomandi, Maziar
Abstract: Accurate estimation of the static and dynamic wind loads on heliostats based on detailed measurement and characterisation of turbulence is crucial to avoid structural failure and reduce the cost of the structural heliostat components. Wind load predictions for heliostats are not specified in design standards for buildings because of a heliostat's non-standard shape and the variations of wind velocity and turbulence in the lowest 10 m of the atmospheric boundary layer (ABL). This paper reviews the static and dynamic wind loads on heliostats in the most unfavourable operating and stow positions, with a focus on the aerodynamic effects related to the heliostat structural component geometry, turbulence parameters in the ABL and field spacing. An increased resolution of field-scale wind measurements at heliostat field sites is recommended to fully characterise the ABL turbulence, as the high-intensity gusts over shorter durations at heights below 10 m lead to high-amplitude displacements with larger frequencies than observed in standard building structures. Increased understanding and development of aerodynamic wind load predictions for heliostats, based on their critical scaling parameters and local wind conditions, would increase the accuracy of annual field efficiency models through an improved resolution of operating load data and reduce the capital cost of structural components in power tower plants.